PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI, TINGKAT PENDIDIKAN, DAN PENGALAMAN KERJA TERHADAP KUALITAS LAPORAN KEUANGAN PADA LEMBAGA PERKREDITAN DESA (LPD) SE-KECAMATAN MENGWI - Ni Luh Mulya Dewi; Ni Wayan Yuniasih (UNHI Press, 2021)
Financial reports are the result of a brief recording process in the form of financial data and activities of a company which aims to provide an overview of the financial condition, results of operations, and company performance at a certain time or for a certain period of time. The quality of financial reports has a very important role in helping make decisions regarding the operations of the entity or organization.This study aims to determine the effect of the use of information technology, level of education, and work experience on the quality of financial reports. This research was conducted at LPD in Mengwi District. The sample in this study were 113 employees. The sampling method used was purposive sampling. The data analysis technique used in this research is descriptive statistics, validity test, reliability test, classical assumption test, multiple linear regression, coefficient of determination, F test, and t test. The results showed that the information technology utilization variable had a positive and significant effect on the quality of financial reports. The level of education has a positive and significant effect on the quality of financial reports. Work experience has a positive and significant effect on the quality of financial reports.